A ANALISA KUALITAS BIOBRIKET NON KARBONISASI BIJI BUAH MERAH DENGAN PEREKAT PATI SAGU - Paga', Bertha Ollin; Reniana (Jurnal Agritechno, 2024)
Dependence on fossil fuels has not been reduced so that demand for this fuel is increasing and it is feared that it will run out quickly. Therefore, there is a need for non-fossil fuel alternatives such as biobriquettes which come from organic waste. The research aims to determine the characteristics of non-carbonized red fruit seed biobriquettes and to determine the effect of variations in the concentration of adhesive on the quality of biobriquettes. The research was conducted experimentally using the Completely Randomized Design (CRD) method. The sampling technique is a simple random sampling technique. Data collection was carried out directly through testing and measuring research variables. The data obtained was then tested and analyzed using Microsoft Excel and presented in the form of tables and graphs. The results obtained showed that the water content of the biobriquettes ranged from 10.75% to 11.04%, density between 0.39-0.45 gr/cm3, ash content between 4.49 - 4.67% and combustion rate between 3.31 - 4.25 gr/minute. The higher the adhesive formulation, the higher the water content and density of the biobriquettes produced. However, the ash content and combustion rate decrease if the adhesive formulation is increased